Oxygen Consumption and Sulfate Reduction in Vegetated Coastal Habitats: Effects of Physical Disturbance - Brodersen, Kasper Elgetti; Trevathan-Tackett, Stacey M.; Nielsen, Daniel A.; Connolly, Rod M.; Lovelock, Catherine E.; Atwood, Trisha B.; Macreadie, Peter I. (Frontiers in Marine Science, 2019)
Vegetated coastal habitats (VCHs), such as mangrove forests, salt marshes and seagrass meadows, have the ability to capture and store carbon in the sediment for millennia, and thus have high potential for mitigating global carbon emissions. Carbon sequestration and storage is inherently linked to the geochemical conditions created by a variety of microbial metabolisms, where physical disturbance of sediments may expose previously anoxic sediment layers to oxygen (O2), which could turn them into carbon sources instead of carbon sinks. Here, we used O2, hydrogen sulphide (H2S) and pH microsensors to determine how biogeochemical conditions, and thus aerobic and anaerobic metabolic pathways, vary across mangrove, salt marsh and seagrass sediments (case study from the Sydney area, Australia). We measured the biogeochemical conditions in the top 2.5 cm of surface (0-10 cm depth) and experimentally exposed deep sediments (> 50 cm depth) to simulate undisturbed and physically exposed sediments, respectively, and how these conditions may affect carbon cycling processes. Mangrove surface sediment exhibited the highest rates of O2 consumption and sulphate (SO42-) reduction based on detailed microsensor measurements, with a diffusive O2 uptake rate of 102 mmol O2 m-2 d-1 and estimated sulphate reduction rate of 57 mmol Stot2- m-2 d-1. Surface sediments (0-10 cm) across all the VCHs generally had higher O2 consumption and estimated sulphate reduction rates than deeper layers (> 50 cm depth). O2 penetration was < 4 mm for most sediments and only down to ~1 mm depth in mangrove surface sediments, which correlated with a significantly higher percent organic carbon content (%Corg) within sediments originating from mangrove forests as compared to those from seagrass and salt marsh ecosystems. Additionally, pH dropped from 8.2 at the sediment/water interface to < 7-7.5 within the first 20 mm of sediment within all ecosystems. Prevailing anoxic conditions, especially in mangrove and seagrass sediments, as well as sediment acidification with depth, likely decreased microbial remineralisation rates of sedimentary carbon. However, physical disturbance of sediments and thereby exposure of deeper sediments to O2 seemed to stimulate aerobic metabolism in the exposed surface layers, likely reducing carbon stocks in VCHs.